Progressive underplating of mafic material at mid-crustal depth beneath Ischia volcano, Italy - Irene Bianchi; Giuseppe Pezzo; Guido Giordano; Claudio Chiarabba (Communications Earth & Environment, 2023)
Abstract The destructive (Mw 3.9) earthquake of 21 August 2017 re-opened the question on where magma resides at the Ischia island volcano. The peculiar complexity of the seismic source initiated the debate on the involvement of fluid-related processes, but the magmatic origin of the event remains uncertain. Here we use ground displacement and broadband seismic data to investigate the magmatic system of Ischia volcano, where progressive underplating of mafic material at mid-crustal depth feeds the deep structures, which are characterized by exceptionally high seismic velocity and are connected with a shallow crystal mush. Although no direct evidence of large molten volumes was found, strong anisotropy suggests that the crystal mush is pervaded by magma-intruded dykes. We propose that the 2017 event was due to a negative tensile deformation caused by depressurization of supercritical fluids along a shallow southwest (SW-)-dipping fault defined by receiver functions (RFs) data, which acted as a valve regulating the overpressure of deep magmatic fluids.